Branding Strategi Bagi Para Pelaku UMKM Kelurahan Kepatihan Kulon - Novi Ria Rahmawati; Rohmawan Adi Pratama; Dama Yuninata; Eva Yuniarti Utami; Wahyu Agung Setyo (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
This research is motivated by the lack of knowledge and ability of MSME actors to carry out product branding, especially in the Kepatihan Kulon sub-district. One of these problems is that the majority of MSMEs have not found a brand to attract customers and packaging that still does not attract buyers and there is limited information regarding product branding. To overcome this problem, it is necessary to carry out research and assistance. The aim of this research is to provide assistance and introduction to creating NIB accounts and checking business names and logos as well as assistance and creating the latest logos for selected MSMEs. The method in this research uses the PAR (Participatory Action Research) method to make it easier for researchers to define problems and provide action as a solution to the problems that have been defined. The results of this research explain that so far MSMEs in the Kepatihan Kulon sub-district have only prioritized taste without paying attention to branding and packaging, so the hopes of this assistance for MSMEs can be higher than before. Apart from that, creating an NIB account is expected to make MSMEs more concerned about the legality of their business.